2019
DOI: 10.1111/gfs.12416
|View full text |Cite
|
Sign up to set email alerts
|

Heavy grazing effects on stem elongation and internode allometry: Insights from a natural pasture grass

Abstract: Limited plant stem elongation is hypothesized to be the primary cause of decreased plant growth in response to long‐term heavy grazing (LHG). However, it remains largely unknown how LHG‐induced changes in stem elongation are mediated by internode traits. Accordingly, we experimentally investigated the effects of LHG (defined as twice the stocking rate recommended by the local government) on plant stem elongation and internode allometry in Leymus chinensis in Xilinhot, Inner Mongolia, China. Plant size and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Various adaptation strategies in the aboveground organs, such as increased stem elongation and specific leaf area for light capturing, are essential for acquiring more resources. Specifically, L. chinensis has a high light compensation and light saturation points (Liu et al 2019;Murphy and Dudley 2009). In this study, historically grazed plants had higher leaf biomass allocation when grown with stranger neighbors than when grown with kin (increasing from 32.67% to 36.90%), which is consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Various adaptation strategies in the aboveground organs, such as increased stem elongation and specific leaf area for light capturing, are essential for acquiring more resources. Specifically, L. chinensis has a high light compensation and light saturation points (Liu et al 2019;Murphy and Dudley 2009). In this study, historically grazed plants had higher leaf biomass allocation when grown with stranger neighbors than when grown with kin (increasing from 32.67% to 36.90%), which is consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…), and tall wheatgrass at a planting ratio of 1:1:1 produced the highest annual herbage yield that was 32.13%, 5.78%, and 21.34% higher, respectively, than alfalfa single planting, a mixture of alfalfa and smooth brome, and a mixture of smooth brome and tall wheatgrass in the Hexi Corridor, China (T. Wang, Cao, Liu, et al, 2022; X. Wang, Cao, Wang, et al, 2022). Additionally, a further study carried out in Inner Mongolia, China, showed that a mixture of alfalfa and tall wheatgrass, with the planting ratios of 1:1, 2:1, and 3:1, produced 15 170–17 100 kg ha –1 DMY, which was approximately three times higher than that of a pure stand of tall wheatgrass and twice that of a pure stand of alfalfa (Liu et al, 2022). Therefore, legume–grass mixtures (alfalfa–tall wheatgrass) may play a role in the construction of the “Coastal Grass Belt.” However, alfalfa is more sensitive to waterlogging and higher soil salinity; for instance, in soils with salinity over 0.4%, such a mixture may have a risk of low productivity.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are relevant for further investigating the mechanisms underlying the response of forage grasses to grazing and grassland productivity formation and productivity decay under grazing. Studies have suggested that the response of steppe plants to grazing is mainly reflected in the growth pattern of plants, with the most obvious indicators being stems and leaves of whole plants (Liu et al, 2019; Orwin et al, 2018; Wang et al, 2021). In a typical grassland under grazing in Inner Mongolia, plant height and biomass in Agropyron cristatum were the factors that were altered to the highest degree, whereas leaf number (LN), length, and width hardly changed (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%